How do Indonesian Teachers Use Teaching Materials?: English Teachers Perception - Banun Havifah cahyo Khosiyono (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2021)
This report is part of a larger study concerning teachers perception towards teaching materials and their effectiveness on professional development (PD) in Indonesia. This case study attempted to explore how the Indonesian teachers perceptions towards the use of English teaching materials for vocational students in Indonesia. Seven out of thirteen English teachers of vocational schools in Indonesia involved in this project were interviewed and observed to use the teaching English materials. Findings show that the teachers believed that they had some considerations to check what was contained in the teaching materials; their perceptions were influenced by some factors such as experience, needs, situation, students interest, students ability, workshop, and references; and the deficient time and different views among teachers were two major problems faced by the teachers when conducting textbook selection and analysis.